DEVELOPING ENGLISH MATERIALS FOR CHARACTER BUILDING BASED ON 2013 CURRICULUM FOR EIGHTH GRADE STUDENTS - Imroatul Hasanah (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2016)
This research developed English Instructional materials for character building based on 2013 Curriculum. The research was carried out in a class of 8th graders of SMP Darul Falah Blitar.  The 23 students were involved in this research in the phase of obtaining information, needs analysis and trying out. The result of needs analysis became the basis of how the researcher composed the English instructional materials with Scientific Approach, official approach of 2013 Curriculum. In the product, an English textbook, the four skills are balance improved; listening, speaking, reading and writing. All of the materials are appropriate with 2013 Curriculum and the contents refer to students’ character building. The materials are for a year of 8th grade which are packaged into seven units. All the steps of learning and exercises in the materials are based on Scientific Approach which has five steps: observing, associating, experimenting, associating and communicating.